Planning to fight speculation: outstanding influences on land rent - Emília Malcata Rebelo (2012)
The core concern of this chapter consists in raising the problem of speculation and of greediness in converting agricultural into urban land in development processes, current in developed societies. Speculation springs as a counterpart of a succession of conceptual and operational flaws, inconsistencies and contradictions in juridical, planning and fiscal systems, which fuels the exacerbated interests of the agents straight or indirectly involved in property markets. A strategic assessment of this problem, under different perspectives, remits to the need to deal with the question of land rent and surplus-values, as they stand in the basis of its resolution. Within this scope, this article proposes and develops a methodology for the evaluation and computation of surplus values that is applied to the Portuguese land and real estate realities. Inferences and conclusions are drawn considering how legal, planning, fiscal, socio-economic and agents´ behaviour perspectives shall deal with the surplus-values question, in order to efficiently solve the problem of speculation.